Kompetensi Kepribadian Guru Pendidikan Agama Islam dalam Pembentukan Karakter Siswa - Tanamal, Dima Toni; Fadhil, Muhammad; Yunus, Abdullah (Journal of Educational Research, 2024)
This article discusses the personality competency of Islamic religious education teachers in the formation of student character, and the supporting and inhibiting factors as well as how Islamic religious education teachers' efforts in the formation of student discipline character at SMP Negeri Ahmad Dahlan, Jambi City. This article comes from qualitative research with data collection through observation, interviews, and documentation as well as data analysis which includes data collection, data reduction, data presentation, and data verification. The results of the study indicate that there are indicators of personality competency possessed by teachers, including; acting in accordance with religious, legal, social and cultural norms, having noble morals, a stable personality, being mature and wise. Other indicators include; being authoritative, showing work ethic, and upholding the teacher's code of ethics. Artikel ini membahas tentang kompetensi kepribadian guru pendidikan agama Islam dalam pembentukan karakter siswa, dan faktor pendukung dan penghambat sekaligus bagaimana upaya guru pendidikan agama Islam dalam pembentukan karakter disiplin siswa di SMP Negeri Ahmad Dahlan Kota Jambi. Artikel ini berasal dari penelitian kualitatif dengan pengumpulan data secara observasi, wawancara, dan dokumentasi serta analisis data yang meliputi pengumpulan data, reduksi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan adanya indikator tentang kompetensi kepribadian yang dimiliki guru antara lain; bertindak sesuai norma agama, hukum, sosial dan kebudayaan, berakhlak mulia, kepribadian yang stabil, dewasa dan arif. Indikator lainnya antara lain; beribawa, menunjukkan etos kerja, dan menjunjung tinggi kode etik guru.